Inspiration and the Oulipo - Chris Andrews (Studies in 20th & 21st Century Literature, 2005)
In the Ion and the Phaedrus Plato establishes an opposition between technique and inspiration in literary composition. He has Socrates argue that true poets are inspired and thereby completely deprived of reason. It is often said that the writers of the French collective known as the Oulipo have inverted the Platonic opposition, substituting a scientific conception of technique—formalization—for inspiration. Some of the group's members aim to do this, but not the best-known writers. Jacques Roubaud and Georges Perec practice traditional imitation alongside formalization. Imitation is a bodily activity with an important non-technical aspect. Raymond Queneau consistently points to an indispensable factor in literary composition that exceeds both formalization and imitation but is inimical to neither. Sometimes he calls this factor "inspiration"; sometimes he speaks of "the unknown" and the "the unpredictable," which must confirm the writer's efforts and intentions. The lack of consensus within the Oulipo on the question of inspiration is not a fault or a weakness, since the group has never claimed to adhere to a unified doctrine. However, to present Queneau as a radical formalist is to distort his poetics.
Keywords: Ion; Phaedrus; Plato; Socrates; Oulipo; Platonic opposition; formalization; poet; poetry; Jacques Roubaud; Georges Perec; imitation; Raymond Queneau; literary composition; composition; inspiration; unknown; the unknown; the unpredictable; unpredictable; poetics